Analisis Kadar Vitamin C Pada Air Mawar Dan Limbah Air Bunga Mawar Merah (Rosa damascena Mill) Dengan Metode Spektrofotometri UV-VIS - Diyan Sakti Purwanto; Riyan Setiyanto; Putri Arsela (Fakultas Farmasi Universitas Setia Budi, 2024)
Red roses are a type of rose that has a distinctive fragrance and a sharp red color. Red roses contain tannins, geraniol, flavonoids and vitamin C which can act as antioxidants. This research aims to measure vitamin C levels from rose water and red rose flower waste. This research method is experimental research which is used to find the effect of certain treatments or treatments under controlled conditions. The samples used were rose water and red rose flower waste. The extraction method used is distillation with distilled water as a solvent. The comparison solution used was ascorbic acid. Vitamin C levels were determined using the UV-Vis spectrophotometry method. The results of determining vitamin C levels showed that the vitamin C levels in red rose waste were greater, namely 2.958 ± 0.018 mg/g.